2018
DOI: 10.1177/1440783318816761
|View full text |Cite
|
Sign up to set email alerts
|

Now, where were we?’: The highs and lows of hunting data with a research pack

Abstract: The boundaries of the social have been stretched by recent scholarship in sociological animal studies. Social theory has been challenged by the posthuman turn (Cudworth, 2011a;Peggs, 2012; Taylor and Signal, 2011), and empirical work on families and households, popular culture, rurality, work and even sleep has begun to open up to the presence of the myriad other creatures that make up social worlds (respectively Charles, 2016;Cole and Stewart, 2014;Wilkie, 2010;Coulter, 2015; Hsu 2017). Much of this research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Veissier and Miele (2014; also Birke & Hockenhull, 2012) have suggested that genuinely multispecies research needs multi‐ or inter‐disciplinary approaches involving research teams with expertise in the science of animal behavior as well as social sciences. I have much sympathy with this suggestion and am conscious of the human bias in this project (Cudworth, 2018). Despite such caveats, ethnographic observation, conversations, and interviews do enable non‐humans to be present to some degree, in the data.…”
Section: Methods and Datamentioning
confidence: 99%
“…Veissier and Miele (2014; also Birke & Hockenhull, 2012) have suggested that genuinely multispecies research needs multi‐ or inter‐disciplinary approaches involving research teams with expertise in the science of animal behavior as well as social sciences. I have much sympathy with this suggestion and am conscious of the human bias in this project (Cudworth, 2018). Despite such caveats, ethnographic observation, conversations, and interviews do enable non‐humans to be present to some degree, in the data.…”
Section: Methods and Datamentioning
confidence: 99%
“…This request in itself notably signalled to human participants (and to readers) that the wishes and bodily autonomy of non-human animals (in not being forcibly moved into the interview zone) were to be respected, constructing them as valued subjects rather than research objects. Of course, multi-species interviews introduce some new challenges, namely that non-human animals did not seem to particularly know or care that the interview was taking place (see also Cudworth, 2018) and many an interview was punctuated by non-human animal vocalisations:…”
Section: Researching With Companion Animalsmentioning
confidence: 99%
“…It does not reflect the material conditions of animal companions who are legally defined as property with minimal welfare safeguards in law. None of the human participants in my study used this term, describing themselves and others as ‘owners.’ (Cudworth 2018 : 500)…”
Section: The Impact Of Disasters On Companion Animalsmentioning
confidence: 99%